2020
DOI: 10.1002/celc.202001295
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐ and Nanotube‐Modified Electrodes: Response of Drop‐Cast Surfaces

Abstract: The morphology of electrodes modified by drop casting layers of multi‐walled carbon nanotubes (MWCNTs) and platinum nanoparticles (PtNPs) is investigated and shown to exhibit significant heterogeneity, both in the form of ‘patchy’ surfaces and of ‘coffee rings’ formed after evaporation of the carrier solvent. The variation of the heterogeneity with total average coverage is studied and the consequences for quantitative analytical voltammetry assessed. Specifically, the oxidation of bromide in aqueous solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…According to the optical microscopy images shown in Figure 1b, a ring‐like pattern was formed on the surface of electrode after the drop casting of Pt nanoparticles, so‐called the coffee ring pattern [33] . It was previously characterized by SEM [34] and shown that although most of the particles are deposited as part of the ‘ring’ a few particles remain randomly distributed around the centre of the drop cast (Figure 1c) [34] but which is mostly empty of deposit. The average particle‐particle distances even in the centre for the mass drop casted were shown to be sufficiently small so as to allow diffusional overlap so that analyte diffusion to the full geometric area of the electrode was observed [34] …”
Section: Methodsmentioning
confidence: 90%
“…According to the optical microscopy images shown in Figure 1b, a ring‐like pattern was formed on the surface of electrode after the drop casting of Pt nanoparticles, so‐called the coffee ring pattern [33] . It was previously characterized by SEM [34] and shown that although most of the particles are deposited as part of the ‘ring’ a few particles remain randomly distributed around the centre of the drop cast (Figure 1c) [34] but which is mostly empty of deposit. The average particle‐particle distances even in the centre for the mass drop casted were shown to be sufficiently small so as to allow diffusional overlap so that analyte diffusion to the full geometric area of the electrode was observed [34] …”
Section: Methodsmentioning
confidence: 90%
“…Taking the area of the GCE (7.06 mm 2 ) and the average NP size (35 nm) a 2 μL (1 mg/ml) dispersion (containing NPs of 35–50 nm range) can form ca 1–2 NP layers averaged over a 3 mm diameter GCE assuming close packing and a uniform deposition covering exclusively the entire disc area. However, some unavoidable local NP agglomeration/aggregation is well known [17] to plague the drop‐casting method. Significant heterogeneity was observed for the TiC NP deposits microscopically as detailed in the SI with well‐separated clumps of accumulated particles evident.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their biocompatibility, MWCNTs are ideal candidates for biomolecule loading, thus significant research is being conducted to advance these models, however, major challenges in the way of nanotube pre-processing remain. The formation of MWCNT agglomerations have been suggested to occur due to the hydrophobicity of the sp 2 carbon sidewalls and the strong π-π stacking interactions between individual carbon nanotubes [25,26]. The surface of unmodified MWCNTs result in a shortage of hydrogen bonding with water molecules.…”
Section: Mwcnt Dispersibilitymentioning
confidence: 99%